2009
DOI: 10.1158/1055-9965.epi-09-0232
|View full text |Cite
|
Sign up to set email alerts
|

Race/Ethnicity Has No Effect on Outcome for Breast Cancer Patients Treated at an Academic Center with a Public Hospital

Abstract: Background: African American women have a higher breast cancer mortality rate than Caucasian women. To understand this difference, socioeconomic status (SES) needs to be controlled, which can be achieved by evaluating outcome within a population that is underinsured or low SES. We elected to examine the effect of race/ethnicity on outcome of patients with operable breast cancer by evaluating outcome in a population with low SES and similar access to care. Methods: From a prospective breast cancer database crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 16 publications
3
17
0
Order By: Relevance
“…It found that black patients had a poorer breast cancer-specific survival rate compared to non-Hispanic white patients, but that after adjustment for clinical and sociodemographic factors this difference was no longer statistically significant. Similar attenuation was seen in another study that evaluated breast cancer outcomes in a population with low SES and similar access to health care [5]. 60% of the patients in the two hospitals studied were blacks and over two-thirds of patients had either Medicaid coverage or no insurance, and here 5-year overall survival rates for black and Caucasian patients were similar.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It found that black patients had a poorer breast cancer-specific survival rate compared to non-Hispanic white patients, but that after adjustment for clinical and sociodemographic factors this difference was no longer statistically significant. Similar attenuation was seen in another study that evaluated breast cancer outcomes in a population with low SES and similar access to health care [5]. 60% of the patients in the two hospitals studied were blacks and over two-thirds of patients had either Medicaid coverage or no insurance, and here 5-year overall survival rates for black and Caucasian patients were similar.…”
Section: Discussionsupporting
confidence: 82%
“…We demonstrate here that many breast cancer disparities persist after adjusting for various aspects of these disparities. Other studies with more detailed individual level data have shown that some disparities are attenuated or disappear after adjusting for certain factors, while other show that they persist [5, 9, 12, 24, 25]. For example, one study compared breast cancer outcomes among underinsured black and non-Hispanic white patients treated in an equal healthcare access setting over a ten year period (1997-2006) [12].…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have shown that African-American patients have worse breast cancer outcomes, these studies generally did not account for factors such as socioeconomic status and differences in treatment received. All patients in our study received standardized treatment and surveillance protocols, and ethnicity was not demonstrated to be an independent risk factor for decreased survival, which is consistent with more recent studies that have examined the impact of racial and socioeconomic factors on outcomes in breast cancer [19].…”
Section: Discussionsupporting
confidence: 89%
“…22 In an analysis of patients undergoing treatment for lung cancer, Farjah and colleagues found that black patients were less likely to undergo surgical resection than white patients; however, racial differences in receiving optimal therapy did not affect outcome. The authors concluded that perceptions about cancer treatment and limited access to care might have a more dominant role in perpetuating racial disparities than previously recognized.…”
Section: Discussionmentioning
confidence: 99%